2005
DOI: 10.1309/e9qp-vq6g-2fbv-mj3b
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Laboratory Turnaround Time Outliers Can Reduce Emergency Department Patient Length of Stay

Abstract: Poor core laboratory performance that causes delays in diagnosis and treatment is an impediment to optimal patient care, particularly in high-volume patient care areas such as the emergency department (ED). To evaluate the impact of laboratory performance on patient care outcomes, we obtained data from 11 hospitals related to laboratory test turnaround time (TAT) parameters and ED patient throughput. We observed that the average length of stay (LOS) in the ED correlated significantly with the percentage of tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 8 publications
1
49
0
2
Order By: Relevance
“…In the United States for instance, Steindel and Howanitz reported that 90% of potassium tests were ordered and reported in 69 minutes or less in Half of laboratories surveyed while STAT chemistry tests had average TAT of less than I hr in 11 hospitals surveyed in another study. 23,24 However, the long TAT appear to be in keeping with what was obtained in a survey in Iran, a developing country. In this study, the TAT for 90% of emergency tests was 3.5 hours while the mean total TAT was 2.28 hours, with a median of 2 hours.…”
Section: Frequencysupporting
confidence: 78%
See 1 more Smart Citation
“…In the United States for instance, Steindel and Howanitz reported that 90% of potassium tests were ordered and reported in 69 minutes or less in Half of laboratories surveyed while STAT chemistry tests had average TAT of less than I hr in 11 hospitals surveyed in another study. 23,24 However, the long TAT appear to be in keeping with what was obtained in a survey in Iran, a developing country. In this study, the TAT for 90% of emergency tests was 3.5 hours while the mean total TAT was 2.28 hours, with a median of 2 hours.…”
Section: Frequencysupporting
confidence: 78%
“…Rapid TAT for emergency tests are frequently due to widespread use of POCT. 23,24,27 Critical conditions often require serial monitoring of laboratory results to enable rapid decisions so as to avoid subsequent avoidable complications. POCT is therefore ideally suited for this purpose.…”
Section: Frequencymentioning
confidence: 99%
“…Certain studies suggest that the TAT of laboratory tests directly influences the duration of stay of patients in the Emergency Department (ED) [5], as a reduction of laboratory TAT reduces ED stay [6], and hence enhances the safety and satisfaction of patients [7]. Decreasing the TAT of laboratory tests, help in reducing overcrowding in the ED [8].…”
Section: Introductionmentioning
confidence: 99%
“…Nestas situações, cerca de 60% das informações de prontuários médicos são relacionados com exames laboratoriais, concluindo que atrasos nos resultados causam atrasos em diagnóstico e tratamento (5) .…”
Section: Confiabilidadeunclassified
“…Existem empresas que se pautam pela estratégia da flexibilidade, inserindo sempre novos produtos no mercado, assim como outras que optam pela velocidade como o seu principal diferencial, entregando seus resultados com Adaptada de Slach, N. (5) …”
Section: Figura 4 -Matriz De Importância/desempenho No Mercado De Apoiounclassified